The Common Retroviral Insertion Locus Dsi1 Maps 30 Kilobases Upstream of the P1 Promoter of the Murine Runx3/Cbfa3/Aml2 Gene - Stewart, Monica (American Society for Microbiology, 2002)
The Dsi1 locus was identified as a common integration site for Moloney murine leukemia virus (MLV) in rat thymic lymphomas, but previous efforts to identify a gene affected by these insertions were unsuccessful. We considered the Runx3 gene a potential candidate on the basis of genetic mapping which showed that Dsi1 and Runx3 are closely linked on mouse chromosome 4 and the precedent of the related Runx2 gene, which emerged recently as a Myc-collaborating gene activated by retroviral insertion in thymic lymphomas of CD2-MYC mice. We now report the physical mapping of the Dsi1 locus to a site 30 kb upstream of the distal (P1) promoter of the murine Runx3 gene. Comparison with the syntenic region of human chromosome 1 shows that the next gene is over 250 kb 5′ to Runx3, suggesting that Runx3 may be the primary target of retroviral insertions at Dsi1. Screening of CD2-MYC lymphomas for rearrangements at Dsi1 revealed a tumor cell line harboring an MLV provirus at this locus, in the orientation opposite that of Runx3. Proviral insertion was associated with very high levels of expression of Runx3, with a preponderance of transcripts arising at the P1 promoter. These results confirm that Runx3 is a target of retroviral insertions at Dsi1 and indicate that Runx3 can act as an alternative to Runx2 as a Myc-collaborating gene in thymic lymphoma.